Predictors of mortality and length of stay in patients with hospital-acquired Clostridioides difficile infection: a population-based study in Alberta, Canada. Issue 1 (September 2019) - Leal, J.; Ronksley, P.; Henderson, E.A.; Conly, J.; Manns, B.
Summary: In a population-based, five-year retrospective cohort study of 5304 adult patients with hospital-acquired Clostridioides difficile infection across Alberta ( N =101 hospitals), 30-day all-cause and attributable mortality were 12.2% and 4.5%, respectively. Patients >75 years of age had the highest odds of attributable mortality (odds ratio (OR) 9.34, 95% confidence interval (CI) 2.92–29.83) and largest difference in mean length of stay (11.7 days, 95% CI 8.2–15.2). A novel finding was that elevated white blood cell count at admission was associated with reduced attributable mortality (OR 0.67, 95% CI 0.50–0.90) which deserves further study. Advancing age was incrementally and significantly associated with all outcomes.